PVA/SA/MXene dual‐network conductive hydrogel for wearable sensor to monitor human motions. Issue 7 (6th September 2021) - Wang, Tingting; Wang, Jinqing; Li, Zhangpeng; Yue, Mingqiang; Qing, Xiaoli; Zhang, Pengxia; Liao, Xiaozhu; Fan, Zengjie; Yang, Shengrong
Abstract: Conductive hydrogels with high flexibility, superior formability, good mechanical elasticity, and excellent biocompatibility have emerged as promising materials for broad applications in flexible/wearable electronic devices. In this work, a conductive dual‐network PVA/SA/MXene hydrogel (PSM‐h) composed of polyvinyl alcohol, sodium alginate, and MXene (Ti3 C2 Tx ) is constructed by a green method without using chemical crosslinking agents. The resultant hydrogel with dual‐network feature shows excellent cytocompatibility (no toxicity for human umbilical cord mesenchymal stem cells), high stretchability (up to 263%), and superior anti‐fatigue ability (stretched up to 1000 cycles). More importantly, PSM‐h based strain sensor presents good sensing sensitivity with a fast response time (62.5 ms) and a low detection limit even under a very slight strain of 0.2%. In terms of the practical application, the PSM‐h based strain sensor can be applied to detect and distinguish various human motions. Abstract : A conductive dual‐network PVA/SA/MXene hydrogel (PSM‐h) composed of polyvinyl alcohol (PVA), sodium alginate (SA), and MXene (Ti3 C2 Tx ) is constructed by a green method without using chemical crosslinking agents, which possesses excellent cytocompatibility, high stretchability, and superior anti‐fatigue ability. Moreover, PSM‐h based strain sensor presents good sensing sensitivity with a fast response time and a low detection limit, which can find practical applications in detecting and distinguishing various human motions.